Engineering Technology Fish Farming of Snakeheads Channa striat ,Bloch, 1793) Based Feed Vitamin C Increase to Superior Quality Using Microsatellite - Istiyanto Samidjan; Diana Rachmawati (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
Objectives for snakeheads farming Cngineered to produce superior products based artificial diet eenrichment vitamin C with different doses and the use of microsatellites to increase growth and determine the superior quality. Methods February to November 2017 Examined the Effect of artificial feed Enriched with vitamin C doses per 100 g feed were given 0 mg (T1), 12 mg (T2), 24 mg ,and 36 mg (T3), 48 mg (T4) were using a completely randomized design (CRD) and 4 treatments and 3 replications. Furthermore, to determine the superior quality using microsatellite genetic markers to see the genetic code snakeheads. Then the treatment was analyzed by ANOVA and data arrangement of molecular weight DNA, polymorphism were analyzed by Cco-stat and Minitab version 11. The data collected observations of the size of the weight absolute, survival, FCR, molecular weight DNA composition, heterogeneity genotype, polymorphism. The results showed that highest of polymorphism were T3 (weight absolute 169.18 mg) and lowest ppolymorphism treatment T1 (weight absolute 149.25 mg) .Next analysis of polymorphism results using a micro-satellite in treatment (T2, ribbon 3,4), and (T3, ribbons 5.6) and (T4, ribbons 7 and 8) respectively using IS-GB1F 5-CCC TGT ATT TCA TTT CTC CA-3 and IS-GB 1 R 5-ACC AAC ACT GCA ATC TCT CT-3 bright ribbons found in treatment T4 (ribbons 7.8) snakeheads are the results showed that the growth of snakeheads were highest in T3 (with ribbons 205bp allele ladder with 215 bps and 225 bps on the right, Addition as well as having polymorphism is high and. variation of different types also found the number of alleles and heterozygotes.